Shear-mediated ALK5 expression regulates endothelial activation - Pang, Kuin Tian; Ghim, Mean; Sarathchandra, Padmini; Warboys, Christina M.; Yacoub, Magdi H.; Chester, Adrian H.; Weinberg, Peter D. (Biochemical and biophysical research communications, 2023)
Calcific aortic valve disease affects the aortic side of the valve, exposed to low magnitude multidirectional (“disturbed) blood flow, more than it affects the ventricular side, exposed to high magnitude uniaxial flow. Overt disease is preceded by endothelial dysfunction and inflammation. Here we investigate the potential role of the transforming growth factor-β (TGF-β) receptor ALK5 in this process. Although ECs are always subject to shear stress due to blood flow, and their responses to shear stress are important in healthy valve development and homeostasis, low magnitude multidirectional flow can induce pathophysiological changes. Previous work has shown ALK5 to be an important mechanosensor. ALK5 transduces mechanically sensed signals via the activation of the SMAD2/3 transcriptional modulators. However, it is currently unclear precisely how ALK5-mediated shear stress responses translate into pathological changes under conditions of chronically disturbed flow. Here, we demonstrate that ALK5 mechanosensory signalling influences flow-induced endothelial leukocyte adhesion and paracellular permeability. Low magnitude multidirectional flow resulted in downregulation of the receptor, accompanied by increased SMAD2 phosphorylation, in human umbilical vein endothelial cell (HUVEC) monolayers. These changes correlated with elevated monocyte adhesion and significantly increased transendothelial transport of an albumin-sized tracer. These effects were abolished by inhibition of ALK5 kinase activity. Analysis of ALK5 expression patterns in porcine aortic valve tissue corroborated the findings from cell-based experiments. Together, these results suggest that ALK5 has a role in shear stress-associated cardiovascular disease pathology, emphasising the importance of further mechanistic investigations and supporting it as a potential therapeutic target. •Low magnitude multidirectional flow (LMMF) downregulate ALK5 expression in endothelial cells (EC).•LMMF increase SMAD2 phosphorylation in EC.•Inhibition of ALK5 abolishes LMMF-induced monocyte adhesion and transendothelial transport of an albumin-sized tracer.•ALK5 expression is higher in EC of the ventricularis of porcine aortic valve (compared with fibrosa).